Karakteristik Fikih Shahaby (Telaah Historis) - Ahmad Faruq (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2018)
Juris prudence (Fikih Shahaby) here is ijtihad syar'iy amaly law at the time of the Companions of Prophet Muhammad SAW. Not all things related to the shahaby fiqh issue are discussed in this paper, but only prioritize the characteristics with a more sought-after hitoric approach highlighted. Considering the length of the period of companionship, this paper only limits itself to the time of the holy month of friendship, which is only between eleven years and forty one. The spread of various places has a distinctive influence on the development of fiqh, at the very least, the expansion of the religious space in tabi'in circles. This can be understood because each region has different situations, habits and culture in addition to differences in understanding the capacity of the jurists in anticipating problems that arise